The effectiveness of using bingo games in developing year 3 students' vocabulary in SK Sapintas, Sabak Bernam / Noraini Ibrahim - Ibrahim, Noraini (Faculty of Education, 2015)
Vocabulary is a main component in learning English. Learning vocabulary has become a basic need when encountering a new language. The purpose of this study was to investigate the effectiveness of using bingo games to develop students’ vocabulary. The population sample of the study involved 25 students from Year 3 SK Sapintas, SabakBemam. The data was collected using pre and post test, which are the two main research instruments. Next, the data was analyzed and presented in table and chart form. The findings of the study indicated that the students’ result increased after the treatment of using bingo game. 23 out of 25 students showed improvement meanwhile 2 out of 25 students did not show any improvement based on several factors. These findings implied that games can help students to improve their language learning process. In the future teachers should create and add more educational games to help students master the English language in a more fun and meaningful way.